2004
DOI: 10.5194/angeo-22-2283-2004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic turbulent spectra in the magnetosheath: new insights

Abstract: Abstract. The spectrum of the magnetic fluctuations measured by the Cluster satellites in the inner magnetosheath is investigated using the k-filtering technique. On a case study, it is shown first that the wave vectors calculated from the Flux Gate Magnetometer (FGM) data fit well with those determined from the Spatio-Temporal Analysis of Field Fluctuations (STAFF) data for their common range of frequency, which allows one to confirm that the high pass filter applied to STAFF data does not alter the spatial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 17 publications
3
95
0
Order By: Relevance
“…They find that a mirror mode propagating at an angle around 60 • to the background magnetic field dominates the wave field but there are also contributions from Alfvén, slow, and cyclotron wave modes. For the same data interval but for lower frequencies, Sahraoui et al (2004) find similar results, with the mirror modes propagating closer to the orthogonal direction at 80 • . Tjulin et al (2005) confirm the presence of mirror modes for the same interval by analyzing the electric field fluctuations after using both magnetic and electric field as input for the k-filtering.…”
Section: Magnetosheath Crossingsupporting
confidence: 72%
“…They find that a mirror mode propagating at an angle around 60 • to the background magnetic field dominates the wave field but there are also contributions from Alfvén, slow, and cyclotron wave modes. For the same data interval but for lower frequencies, Sahraoui et al (2004) find similar results, with the mirror modes propagating closer to the orthogonal direction at 80 • . Tjulin et al (2005) confirm the presence of mirror modes for the same interval by analyzing the electric field fluctuations after using both magnetic and electric field as input for the k-filtering.…”
Section: Magnetosheath Crossingsupporting
confidence: 72%
“…The collective motion of particles arising due to the diamagnetic currents in such systems stimulates the development of low-frequency drift instabilities. Actually, results of the experimental observations of the spectra of low-frequency fluctuations in the magnetosphere (Sahraoui et al, 2003(Sahraoui et al, , 2004(Sahraoui et al, , 2006Mangeney et al, 2006;Alexandrova et al,, 2006;Narita et al, 2007), ionosphere (Lysak, 1990;Chaston et al, 1999;Stasiewicz et al, 2000;Abel et al, 2006) and experimental plasma devices (Browley and Mazzucato, 1985;Brower et al, 1987;Weissen et al, 1988;Gekelman, 1999), show that the observed fluctuations with the significant amplitude are produced due to the development of drift-Alfvén instability. One of the indications of the instability evolution in magnetized plasma is the shaping of the ordered wavy structures or vortexes, whose collective activity can finally lead to the formation of the turbulent state (Horton, 1990;Tu and Marsch, 1997;Aburjania,12 G. D. Aburjania et al: Model of strong stationary vortex turbulence Following its own logic of development, in the sixties of the last century, the plasma turbulence theory was based on the weak turbulence model when only the weak interaction between modes due to nonlinearity was taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, only a handful of studies have been carried out in recent years (see e.g., Sahraoui et al 2003Sahraoui et al , 2004Mangeney et al 2006;Sahraoui et al 2006;Alexandrova et al 2008b;Yordanova et al 2008;He et al 2011). Two main similarities with solar wind turbulence emerged from those studies: the turbulence in strongly anisotropic (k k ⊥ ) at subproton and electron scales (Sahraoui et al 2004;Mangeney et al 2006;Sahraoui et al 2006) and kinetic instabilities and nonlinear structures are present (Sahraoui et al 2004;Sahraoui 2008;Alexandrova et al 2008b).…”
Section: Electron Scale Turbulencementioning
confidence: 99%
“…Indeed, only a handful of studies have been carried out in recent years (see e.g., Sahraoui et al 2003Sahraoui et al , 2004Mangeney et al 2006;Sahraoui et al 2006;Alexandrova et al 2008b;Yordanova et al 2008;He et al 2011). Two main similarities with solar wind turbulence emerged from those studies: the turbulence in strongly anisotropic (k k ⊥ ) at subproton and electron scales (Sahraoui et al 2004;Mangeney et al 2006;Sahraoui et al 2006) and kinetic instabilities and nonlinear structures are present (Sahraoui et al 2004;Sahraoui 2008;Alexandrova et al 2008b). Major differences with the solar wind do exist, however, e.g., (i) magnetosheath turbulence evolves in a 'confined' space limited by the bow shock and the magnetopause and these boundaries may influence the anisotropy of the turbulence (Sahraoui et al 2006;Yordanova et al 2008), and, (ii) in contrast to the solar wind, the fluctuations are dominated by zero-frequency compressible fluctuations (e.g., mirror modes Sahraoui et al 2006).…”
Section: Electron Scale Turbulencementioning
confidence: 99%
See 1 more Smart Citation